2014
DOI: 10.1007/s00586-014-3189-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of comorbidity on the risks and benefits of spine surgery for degenerative lumbar disorders

Abstract: Purpose The ageing of the population will see a growing number of patients presenting for spine surgery with appropriate indications but numerous medical comorbidities. This complicates decision-making, requiring that the likely benefit of surgery (outcome) be carefully weighed up against the potential risk (complications). We assessed the influence of comorbidity on the risks and benefits of spine surgery. Methods 3,549/4,053 patients with degenerative lumbar disorders, undergoing surgery with the goal of pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 13 publications
3
42
0
1
Order By: Relevance
“…30 In a large series comprising more than 3500 patients with degenerative lumbar disorders, it was shown that the ASA grade has an independent effect on both complications and outcome. 1 Although age was associated with an increase in comorbidity, the effect of comorbidity on complications and outcome was not just an effect of age. 1 Age positively correlated with an increase in complication risk in a prospective assessment of 87 consecutive patients undergoing elective surgery for degenerative thoracolumbar disorders, 31 although it was not clear whether age was simply a surrogate measure of comorbidity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…30 In a large series comprising more than 3500 patients with degenerative lumbar disorders, it was shown that the ASA grade has an independent effect on both complications and outcome. 1 Although age was associated with an increase in comorbidity, the effect of comorbidity on complications and outcome was not just an effect of age. 1 Age positively correlated with an increase in complication risk in a prospective assessment of 87 consecutive patients undergoing elective surgery for degenerative thoracolumbar disorders, 31 although it was not clear whether age was simply a surrogate measure of comorbidity.…”
Section: Discussionmentioning
confidence: 98%
“…1 Although age was associated with an increase in comorbidity, the effect of comorbidity on complications and outcome was not just an effect of age. 1 Age positively correlated with an increase in complication risk in a prospective assessment of 87 consecutive patients undergoing elective surgery for degenerative thoracolumbar disorders, 31 although it was not clear whether age was simply a surrogate measure of comorbidity. In a large retrospective analysis of 174 patients older than 70 years and 311 patients younger than 65 years of age, multiple regression analysis revealed increased age as important risk factor for perioperative complications in patients undergoing lumbar spinal fusion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3 The literature has also shown the ASA class to predict patient satisfaction following lumbar spine surgery. 15 In a study by Mannion and colleagues, the percentage of patients satisfied with surgery was 87%, 85%, and 79% for preoperative ASA classes I, II, and III, respectively, indicating that higher ASA classes were associated with lower percentages of patient satisfaction. In contrast to these studies, our study focused only on patients with lumbar spondylolisthesis; thus, the differing pathology-specific factors may have contributed to the differences reported herein.…”
Section: Discussionmentioning
confidence: 97%
“…Schoenfeld et al [1] identified cardiac disease and an ASA score of > 2 as independent risk factors for medical complications after spine surgery. Mannion et al [17] reported that an increasing ASA score is associated with a higher incidence of perioperative complications. They concluded that the ASA score might be used in preoperative counseling of patients about their perioperative risk.…”
Section: Discussionmentioning
confidence: 99%